Knowledge of and attitude towards human papillomavirus infection and vaccines among nurses at a tertiary hospital in South Africa. (February 2014) - Hoque, M. E.; Monokoane, S.; Van Hal, G.
<x xml:space="preserve">Abstract</x> The purpose of this cross-sectional study was to determine factors contributing to recommending vaccination to patients, using a self-administered anonymous questionnaire given to 345 nurses working at a tertiary hospital in South Africa. The average age of the participants was 37.2 years. About three-quarters (73.3%) of the nurses were aware of HPV and among them, 38.3% knew that HPV is the most common sexually transmitted virus. Nurses had poor knowledge regarding HPV infection and the HPV vaccine. The majority (90.9%) of the nurses intended to recommend the vaccine to their patients. The nurses who mentioned that adolescents and young adults would accept HPV vaccination were more likely to recommend HPV vaccination to their patients (OR = 57.78, p = 0.031). Nurses had a low level of knowledge regarding HPV infection and vaccines but they were willing to recommend the vaccines to their patients. Nurses need to be educated before implementing HPV vaccinations nationwide.